Implementing school nursing strategies to reduce LGBTQ adolescent suicide: a randomized cluster trial study protocol. (December 2016) - Willging, Cathleen; Green, Amy; Ramos, Mary
Abstract Background Reducing youth suicide in the United States (U.S.) is a national public health priority, and lesbian, gay, bisexual, transgender, and queer or questioning (LGBTQ) youth are at elevated risk. The Centers for Disease Control and Prevention (CDC) endorses six evidence-based (EB) strategies that center on meeting the needs of LGBTQ youth in schools; however, fewer than 6 % of U.S. schools implement all of them. The proposed intervention model, "RLAS" (Implementing School Nursing Strategies to Reduce LGBTQ Adolescent Suicide), builds on the Exploration, Preparation, Implementation, and Sustainment (EPIS) conceptual framework and the Dynamic Adaptation Process (DAP) to implement EB strategies in U.S. high schools. The DAP accounts for the multilevel context of school settings and uses Implementation Resource Teams (IRTs) to facilitate appropriate expertise, advise on acceptable adaptations, and provide data feedback to make schools implementation ready and prepared to sustain changes. Methods/Design Mixed methods will be used to examine individual, school, and community factors influencing both implementation process and youth outcomes. A cluster randomized controlled trial will assess whether LGBTQ students and their peers in RLAS intervention schools (n = 20) report reductions in suicidality, depression, substance use, bullying, and truancy related to safety concerns compared to those in usual care schools (n = 20). Implementation progress and fidelity for each EB strategy in RLAS intervention schools will be examined using a modified version of theStages of Implementation Completion checklist. During the implementation and sustainment phases, annual focus groups will be conducted with the 20 IRTs to document their experiences identifying and advancing adaptation supports to facilitate use of EB strategies and their perceptions of the DAP. Discussion The DAP represents a data-informed, collaborative, multiple stakeholder approach to progress from exploration to sustainment and obtain fidelity during the implementation of EB strategies in school settings. This study is designed to address the real-world implications of enabling the use of EB strategies by school nurses with the goal of decreasing suicide and youth risk behaviors among LGBTQ youth. Through its participatory processes to refine and sustain EB strategies in high schools, the RLAS represents a novel contribution to implementation science. Trial registration ClinicalTrials.gov, NCT02875535